Comparison of static friction with self-ligating, modified slot design and conventional brackets (Journal of Applied Oral Science, 2013)
OBJECTIVE: To compare the static frictional forces generated at the bracket/wire interface of stainless steel brackets with different geometries and angulations, combined with orthodontic wires of different diameters. MATERIAL AND METHODS: The frictional forces were evaluated with three different types of metal brackets: a passive self-ligating (SmartClipTM, 3M/Unitek, Monrovia, USA), with a modified slot design (Mini Uni TwinTM, 3M/Unitek, Monrovia, USA) and conventional (Kirium, Abzil, São José do Rio Preto, Brazil). The samples were mounted in a testing device with three different angulations and tested with 0.014" and 0.018" stainless steel wires (American Orthodontics, Sheboygan, USA). The static frictional force was measured using a universal testing machine (DL 500, EMIC®, São José dos Pinhais, Brazil) with a crosshead speed of 1 mm/min. Statistical analysis was performed by two-way ANOVA followed by Bonferroni's post hoc test. RESULTS: There was a significant difference (p